2013
DOI: 10.1128/mbio.00065-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofSalmonellaPathogenicity Island-2 Type III Secretion System Effectors Involved in Intramacrophage Replication of S. enterica Serovar Typhimurium: Implications for Rational Vaccine Design

Abstract: Salmonella enterica serovars cause severe diseases in humans, such as gastroenteritis and typhoid fever. The development of systemic disease is dependent on a type III secretion system (T3SS) encoded by Salmonella pathogenicity island-2 (SPI-2). Translocation of effector proteins across the Salmonella-containing vacuole, via the SPI-2 T3SS, enables bacterial replication within host cells, including macrophages. Here, we investigated the contribution of these effectors to intramacrophage replication of Salmonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
143
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 58 publications
2
143
5
Order By: Relevance
“…Despite this apparent similarity, differences between fibroblasts and cultured macrophages are likely to exist, since in the former cells SPI-2 is used by intracellular S. Typhimurium mainly for survival rather than for proliferation (36,61). Our study also shows that SifA is dispensable for intracellular survival, in marked contrast to the key role of this effector in bacterial growth inside macrophages (47,69). Interestingly, a recent study by Grant et al reported a role of SPI-2 in negatively modulating the growth rate in vivo in phagocytic cells (37).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Despite this apparent similarity, differences between fibroblasts and cultured macrophages are likely to exist, since in the former cells SPI-2 is used by intracellular S. Typhimurium mainly for survival rather than for proliferation (36,61). Our study also shows that SifA is dispensable for intracellular survival, in marked contrast to the key role of this effector in bacterial growth inside macrophages (47,69). Interestingly, a recent study by Grant et al reported a role of SPI-2 in negatively modulating the growth rate in vivo in phagocytic cells (37).…”
Section: Discussioncontrasting
confidence: 45%
“…In RAW264.7 macrophages, the data implicated SPI-2 effectors such as SifA and SifB in bacterial replication/survival but did not reveal any change for mutants lacking SseF or SseG. More recently, the lack of SPI-2 effectors, such as SifA, SseJ, SopD2, SseG, SseF, and SrfH, has been reported to affect the capacity of S. Typhimurium to proliferate within mouse bone marrow-derived macrophages (69). Of these effectors, SseJ, SseG, and SseF play an important role in survival of nongrowing dormant bacteria located in fibroblasts.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, a subset of SPI-2 effectors (PipB2, SifA, SopD2, SseF, SseG, and SseJ) has been shown to control membrane dynamics and the intracellular positioning of the SCV (3,17). S. Typhimurium ⌬pipB2 (18), ⌬sifA (19), ⌬sopD2 (20), ⌬sseF (9), ⌬sseG (9), and ⌬sseJ (21) single mutants are all attenuated for virulence in the mouse model of systemic infection, and with the exception of S. Typhimurium ⌬pipB2, each of these single mutants is deficient for intracellular replication in mouse macrophages (22). Therefore, the action of these effectors should promote bacterial virulence by mediating the intracellular replication of Salmonella through subversion of host cell intracellular trafficking pathways.…”
mentioning
confidence: 99%
“…The genes found to be overexpressed in HD11 and COEC consisted of a cohort of stress response, transport, cell wall and DNA modification, fimbrial, AMPR, and virulence genes. The identification of SPI-1 genes at 1 hpi and an SPI-2 gene at 4 hpi validated the authenticity of the results of the SCOTS experiment, as these genes are known to be involved in invasion and intracellular replication, respectively (11,20,48). The overexpression of SPI-2, SPI-5, and AMPR genes was confirmed by real-time PCR, indicating the utilization of these genes for replication and survival within these chicken cells.…”
Section: Discussionmentioning
confidence: 63%
“…To survive inside macrophages, Salmonella has to defend itself against many host killing factors: low Mg 2ϩ and Ca 2ϩ , acidic pH, and reactive oxygen species (7). To survive in this environment, Salmonella utilizes the components of T3SS-1 and T3SS-2 and the PhoP/PhoQ regulon (10)(11)(12)(13). S. Enteritidis has been shown to colonize the ovary and the reproductive tract within laying hens, with a higher recovery from the ovary than from any other reproductive tissue (14,15).…”
mentioning
confidence: 99%